2018
DOI: 10.1007/978-3-319-99660-8_7
|View full text |Cite
|
Sign up to set email alerts
|

Simple Games Versus Weighted Voting Games

Abstract: A simple game (N, v) is given by a set N of n players and a partition of 2 N into a set L of losing coalitions L with value v(L) = 0 that is closed under taking subsets and a set W of winning coalitions W with v(W ) = 1. Simple games with α = min p≥0 maxW ∈W,L∈L p(L) p(W ) < 1 are known as weighted voting games. Freixas and Kurz (IJGT, 2014) conjectured that α ≤ 1 4 n for every simple game (N, v). We confirm this conjecture for two complementary cases, namely when all minimal winning coalitions have size 3 and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…This is of course not always possible, that is, the core might be empty. This leads to related A partial answer to the conjecture of Freixas and Kurz appeared, together with some results of this paper, in an extended abstract published in the proceedings of SAGT 2018 [20].…”
Section: Introductionsupporting
confidence: 56%
“…This is of course not always possible, that is, the core might be empty. This leads to related A partial answer to the conjecture of Freixas and Kurz appeared, together with some results of this paper, in an extended abstract published in the proceedings of SAGT 2018 [20].…”
Section: Introductionsupporting
confidence: 56%
“…In [5] the conjecture of Freixas and Kurz was verified for simple games with all minimal wining coalitions of size 3 and for simple games with no minimal winning coalitions of size 3. In [5] it was shown that α 2n/7 for general simple games.…”
Section: Introductionmentioning
confidence: 94%
“…⋆ A partial answer to the conjecture of Freixas and Kurz appeared, together with some results of this paper, in an extended abstract published in the proceedings of SAGT 2018[20].…”
mentioning
confidence: 89%
“…We also prove that for graphic simple games, that is, simple games in which every minimal winning coalition has size 2, computing α is NP-hard, but polynomial-time solvable if the underlying graph is bipartite. Moreover, we show that for every graphic simple game, deciding if α < a is polynomial-time solvable for every fixed a > 0.⋆ A partial answer to the conjecture of Freixas and Kurz appeared, together with some results of this paper, in an extended abstract published in the proceedings of SAGT 2018 [20].…”
mentioning
confidence: 94%